Perbandingan Karbon Aktif Tandan Kosong Kelapa Sawit Tidak Teraktivasi dan Teraktivasi H2SO4 0,1m Terhadap Penururnan Cod dan Ph Air Rebusan Kelapa Sawit Melalui Proses Adsorpsi Bacth - Fithry, Dwi Anissa; Sitorus, Oby Vijay; Amanda, Mesy Isni (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The palm oil industry produces liquid waste in the form of palm oil boiled water which has a high organic compound content, causing high Chemical Oxygen Demand (COD) values ​​and unstable pH. This study aims to compare the performance of activated and unactivated OPEFB activated carbon with 0.1 M H2SO4 in reducing COD values ​​and stabilizing the pH of palm oil boiled water through a batch adsorption process. The adsorption process is carried out in batches with variations in adsorbent mass, stirring speed, and certain contact time. Activated activated carbon is prepared using 0.1 M H2SO4 solution, while non-activated activated carbon is used without chemical treatment. The parameters analyzed include COD and pH values ​​before and after the adsorption process. The results of the study showed that 0.1 M H2SO4-activated EFB activated carbon had better adsorption capacity than non-activated activated carbon in reducing COD from palm oil boiled water and producing a pH closer to neutral.